Possibilities to use a virtual opponent for enhancements of reactions and perception of young karate athletes - Petri, K.; Masik, S.; Danneberg, M.; Emmermacher, P.; Witte, K. (International Journal of Computer Science in Sport, 2019)
We conducted a virtual reality (VR) training with ten sessions, performed by fifteen young karate athletes, who responded to attacks of a virtual opponent to improve their response behavior and their decision-making. The control groups continued with their normal training. Results of the Friedman tests with subsequent Dunn-Bonferroni post-hoc-tests and estimation of effect sizes showed that the karate specific response behavior (measured by a movement analysis) improved significantly due to the training. The parameters time for response (as the time for the attack initiation) and response quality improved with large effect sizes for the intervention groups, whereas the control groups demonstrated improvements with only small effect sizes. The unspecific response behavior (analyzed by two forms of the reaction test of the Vienna test system) did not show any significant changes. Paired t-tests revealed an improvement in attack recognition. While in the pretests, the intervention groups responded to late movement stages of the attack (execution of the main phase), they responded to early movement stages (reduction of distance and preparing steps) in the posttests. Furthermore, Friedman-tests and bivariate correlation analysis showed that the intervention groups were highly motivated to perform the VR training because of the new and safe learning conditions.